Debt Report 2022 Edition I - World Bank Group (World Bank, Washington, DC, 2022)
This is the first of three Debt Reports for 2022 to be published online over the course of the year to provide users with data and analysis on external and public debt of low- and middle-income countries. Debt Report 2022 First Edition present summary analyses of the composition of external debt stocks and flows from the regional perspective. It draws out the main messages of the regional and country specific data and incorporates updates to the 2020 data included in IDS 2022. The report also presents updated data on the outcomes of the Debt Service Suspension Initiative (DSSI). The updated dataset was released in December 2021 and is available to users at: https://data.worldbank.org/products/ids.